Reproductive success of Cabralea canjerana (Meliaceae) in Atlantic forest fragments, Brazil - Franceschinelli, Edivani Villaron (Universidad de Costa Rica, 2015)
In Brazil, the Atlantic forest remnants have high biological diversity and a high level of endemism, but very little is known about the reproductive success of native species. Cabralea canjerana is a common tree in the Montane Atlantic forest, and its reproduction is highly dependent on pollinators. In order to contribute with the particular knowledge on this species, we collected data in three fragmented and three continuous forest sites, where the effects of fragmentation on both mutualistic (pollination) and antagonistic (seed predation) interactions were analysed. We determined fruit production and weight of 25 trees per site. The number of seeds and the percentage of predated and aborted seeds were also accessed for seven fruits of 10 trees per site. Pollinator visitation frequencies to flowers were recorded in two forest fragments and in two sites of the continuous forest. Our data showed that plants of C. canjerana produced more fruits (z-value=-8.24; p<0.0001) and seeds per fruit (z-value=-6.58; p=0.002) in the continuous than in the fragmented sites. This was likely due to differences in pollination, because the number of pollinator visits was higher in the continuous forest than in the fragments. Seed abortion (z-value=4.08, p<0.001) and predation (z-value=3.72, p=0.0002), on the other hand, were higher in the fragmented than in the continuous sites. Then, mutualistic and antagonistic interactions were affected by fragmentation, decreasing the reproductive success of the study tree. This study was the first to show a decrease in the reproductive output in forest fragments in an Atlantic forest tree species. This decrease may threaten the population structure and viability of C. canjerana in forest fragments.